2014
DOI: 10.1152/ajpregu.00100.2014
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of omega-3 fatty acid docosahexaenoic acid and palmitate on the circadian transcriptional profile of clock genes in immortalized hypothalamic neurons

Abstract: Diets high in saturated fatty acids (SFAs) are associated with the development of circadian dysregulation, obesity, and Type 2 diabetes mellitus. Conversely, polyunsaturated fatty acids (PUFAs) have recently been identified to improve insulin sensitivity, reduce weight gain, and relieve obesity-induced inflammation. While saturated fatty acids, such as the prevalent dietary fatty acid palmitate, have been implicated in circadian disruption, there is a paucity of studies regarding the effects of PUFAs on circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 53 publications
4
45
0
Order By: Relevance
“…A final concentration of 50 µM was prepared by diluting the stock solution in pre-warmed (37°C) media with 5% FBS as a carrier. This methodology was developed, and certified [14, 29], to avoid potential LPS contamination in BSA-conjugated palmitate. This was still an issue even with “endotoxin-free” BSA where we previously found that the BSA alone had an effect on cellular cytokine expression.…”
Section: Methodsmentioning
confidence: 99%
“…A final concentration of 50 µM was prepared by diluting the stock solution in pre-warmed (37°C) media with 5% FBS as a carrier. This methodology was developed, and certified [14, 29], to avoid potential LPS contamination in BSA-conjugated palmitate. This was still an issue even with “endotoxin-free” BSA where we previously found that the BSA alone had an effect on cellular cytokine expression.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, meal composition may affect the molecular clock system (39). In cell line studies, it has been demonstrated that the fatty acid palmitate can alter circadian expression of clock genes (19,23). This is supported by an in vivo study demonstrating that 3 days on a HFD are sufficient to alter expression of mouse hepatic clock genes, suggesting that the HFD rather than the development of obesity initiates circadian reprogramming (17).…”
Section: G937 Circadian Disruption Of Metabolismmentioning
confidence: 97%
“…The ability of other classes of LCFA differing in the length of their acyl chain and/or in their degree of unsaturation to elicit the activation of these systems has been scarcely assessed to date. The available studies in mammals indicate that neither saturated fatty acids like palmitate (C16:0) nor the presence of two (such as in linoleate, C18:2 n-6) or three (such as in docosahexanoate, C22:6 n-3) double bonds activate fatty acid sensing systems (Gomez-Pinilla and Ying, 2010; Ross et al, 2010; Schwinkendorf et al, 2011; Greco et al, 2014). …”
Section: Nutrient Sensing Mechanisms In Fishmentioning
confidence: 99%